DAMPAK DAN STRATEGI PEDAGANG UMKM BERTAHAN KETIKA DAN PASCA COVID-19: (Studi Kasus: Pedagang UMKM di Kota Tanjung Pinang, Kepri) - Hendra Candra; Nizar Zulkarnain (Journal of Social Science and Multidisciplinary Analysis, 2024)
The impact of the Covid-19 Pandemic is very significant for economic movements in Indonesia, including in Tanjung Pinang City whose income tends to come from the Tourism sector and is closely side by side with MSME traders, then what is the impact and strategy of MSME traders in maintaining and recovering their businesses during and after the Pandemic. The purpose of this study is to determine the impact of the Covid-19 pandemic on MSME traders in Tanjung Pinang City and analyze how strategies are carried out to survive and recover their businesses during and after the Pandemic. This study used qualitative descriptive design with hermeneutic analysis methods and data collection using primary sources with interview and observation techniques. The result of this study is that the average MSME trader in Tanjung Pinang City is affected by the Covid-19 Pandemic, while the strategy used to survive is that they have their own strategies, while the strategy to recover their business after the Covid-19 Pandemic is to continue the strategy that has been done before. The conclusion of this study is that the Covid-19 Pandemic has affected MSME Traders in Tanjung Pinang City, both for traders who sell directly in certain locations, traders who sell online to traders who produce foodstuffs, as for the strategies used by traders during or after the Covid-19 Pandemic are very different according to the line of business they are running.